ANALISIS TINGKAT KESEHATAN BANK MANDIRI DENGAN METODE RBBR PERIODE 2016-2020 - Nadya Octavianne, (2021)
Banks carry out three main activities to collect funds from the public in the form of deposits, channel funds to the public in the form of credit, and provide other services. In this case, the bank is considered as an important intermediary between the parties who are overfunded and underfunded. Therefore, financial institutions are expected to always be in good health. The approach used by Bank Mandiri uses a Risk Based Bank Rating (RBBR) approach with Bank Mandiri's level of health in terms of the Risk Profile aspect (Risk Profile) by measuring Credit Risk (NPL) and Liquidity Risk (LDR), for measuring aspects of Good Corporate Governance (GCG) is reviewed from 11 conditions, while Earnings is measured by calculating Return On Assets (ROA), Net Interest Margin (NIM) and Operating Expenses and Operating Income (BOPO), the last one in the Capital aspect is measured using the Capital Adequacy Ratio (CAR). The purpose of this paper is to find out how the health level of Bank Mandiri by using a risk-based approach during the period 2016 to 2020. The results of this paper will show the health level of Bank Mandiri based on risk profile factors, good corporate governance, profitability and capital which is ranked second.